"تأثير التمرين ألبدني الإيقاعي في بعض المتغيرات البدنية والفسيولوجية للمترهلين بدنياً" - د.عباس فاضل جابر ألخزاعي; د.برع حميد مهدي ألسامرائي (مجلة علوم الرياضة, 2010)
Now being implemented in many satellite channels for the developed world every day and units of physical training rhythmic (Aerobic) through sport practiced morning of music by everyone .. have changed much of the world’s methods to fitness health in order to access the individual to the highest level of fitness and skill and in commensurate with the requirements of the age and skill and physical and psychological health that has been directed our colleagues working in the field of sports medicine, rehabilitation and fitness experts on the need to be units of physical training influential and violent and interesting, not boring and routine ...